Atomic Level Defect Structure Engineering for Unusually High Average Thermoelectric Figure of Merit in n‐Type PbSe Rivalling PbTe. Issue 35 (26th October 2022) - Ge, Bangzhi; Lee, Hyungseok; Huang, Lulu; Zhou, Chongjian; Wei, Zhilei; Cai, Bowen; Cho, Sung‐Pyo; Li, Jing‐Feng; Qiao, Guanjun; Qin, Xiaoying; Shi, Zhongqi; Chung, In
Abstract: Realizing high average thermoelectric figure of merit (ZTave ) and power factor (PFave ) has been the utmost task in thermoelectrics. Here the new strategy to independently improve constituent factors in ZT is reported, giving exceptionally high ZTave and PFave in n‐type PbSe. The nonstoichiometric, alloyed composition and resulting defect structures in new Pb1+ x Se0.8 Te0.2 ( x = 0–0.125) system is key to this achievement. First, incorporating excess Pb unusually increases carrier mobility ( µ H ) and concentration ( n H ) simultaneously in contrast to the general physics rule, thereby raising electrical conductivity ( σ ). Second, modifying charge scattering mechanism by the authors' synthesis process boosts a magnitude of Seebeck coefficient ( S ) above theoretical expectations. Detouring the innate inverse proportionality between n H and µ H ; and σ and S enables independent control over them and change the typical trend of PF to temperature, giving remarkably high PFave ≈20 µW cm −1 K −2 from 300 to 823 K. The dual incorporation of Te and excess Pb generates unusual antisite Pb at the anionic site and displaced Pb from the ideal position, consequently suppressing lattice thermal conductivity. The best composition exhibits a ZTave of ≈1.2 from 400 to 823 K, one of the highest reported for all n‐type PbQ (Q = chalcogens) materials. Abstract : The dual incorporation of Te and excess Pb generates unusual antisite Pb at the anionic site and displaces Pb from the ideal position, which extraordinarily enhances the power factor and depresses thermal conductivity, thereby boosting average ZT to 1.2 from 400 to 823 K, even comparable to the record‐high value for n‐type PbTe.